Evidence of Warming From Long-Term Records of Climate and Permafrost in the Hinterland of the Qinghai–Tibet Plateau - Zhou, Fujun; Yao, Miaomiao; Fan, Xingwen; Yin, Guoan; Meng, Xianglian; Lin, Zhanju (Frontiers in Environmental Science, 2022)
The Qinghai–Tibet Plateau (QTP) is characterized by its extreme climate and dominated by periglacial processes. Permafrost conditions vary greatly, and the recent changes on the QTP are not well known in the hinterland. Here, we examine the changes in climate and permafrost temperatures in several different regions. Climate data were obtained from three weather stations from 1957 to 2019. Annual mean air temperature (Ta) has gradually increased at .031°C/yr–.039°C/yr. Climate warming has been more rapid in the past two decades, particularly during the cold season (November to February). Precipitation has also been slowly increasing during the instrumental record. However, there is pronounced heterogeneity in the seasonal distribution of precipitation, with very little falling between October and April. Ground temperatures and active-layer thickness (ALT) have been investigated over ∼20 years at five sites representative of the hinterland of the QTP. These sites are located along the Qinghai–Tibet Highway, which crosses the permafrost zone and traverses the mountainous area and basin areas. Annual mean ground temperatures within the active layer (Tal ∼ 1 m depth) indicate recent ground warming at all sites, at rates near .05°C/yr. The ALT at five sites has been increasing steadily by 2–9 cm/yr, with an average of 4.6 cm/yr. The temperature near the permafrost table (Tps) has been increasing at .01°C/yr and .06°C/yr, with an average of .03°C/yr. Permafrost temperatures at 15 m depth (Tg) have been increasing by about .01°C/yr–.02°C/yr. The southern boundary (AD site) of the permafrost has warmed the least among the five locations. In high mountainous areas where permafrost temperatures are low (e.g., KLS site), the annual mean Tg has increased by nearly .02°C/yr. The rate of permafrost warming at a basin site (BLH), with relatively high ground temperatures, was approximately .01°C/yr. The GIPL2.0 model simulation results indicate that the annual mean permafrost temperature at 1 m depth at these sites will increase by .6°C–1.8°C in the next 100 years (to 2100) and that ALT will increase by ∼40–100 cm. We also discuss the impacts of permafrost changes on the environment and infrastructure on the QTP. This study provides useful information to understand observed and anticipated permafrost changes in this region, under different shared socioeconomic pathways, which will allow engineers to develop adaptation measures.